ISRAELI EMPIRE AND END-TIMES: A STUDY OF “PAX JUDAICA” IN IMRAN HOSEIN'S ISLAMIC ESCHATOLOGY SUFISTIC INTERPRETATION - Eliansyah, Ivan (Sekolah Tinggi Agama Islam Sadra, 2024)
Since the founding of the state of Israel there has been a series of prolonged conflicts between Israel and the surrounding Arab countries, and especially Palestine. The entire global community was shocked by the issue of the bombardment of women and children in Gaza and Rafah. Amid the chaos of the Western subjectivity lobby and the silence of several influential muslim leaders and the UN, the Islamic and non-Islamic world needs to understand the future roots of Israel’s mysterious agenda through ta’wīl and predictive analysis of Islamic Eschatology initiated by Imran Nazar Hosein. This article examines Israel’s agenda by studying the chronological eschatological concept of “Three Paxes” especially “Pax Judaica” using analytical-descriptive methods. In this qualitative research, researchers used library research by collecting data from several references such as main reference books, journals, videos, and others. According to the findings in this article, in Islamic Eschatology; the agenda is three stages starting in Great Britain (Pax Britannica) then in the US (Pax Americana), and moving on to Israel (Pax Judaica) before finally, the Antichrist appears to take over the throne of King Solomon in Jerusalem. Finally, the conclusion of Israel’s agenda from Imran Hosein’s allegorical interpretation is none other than to prepare a false Jesus (al-Dajjāl) after his systems (control of usury and the monetary system, politics, the emergence of Gog and Magog and biggest war) begin to be fulfilled.